2021
DOI: 10.3389/fgene.2021.728177
|View full text |Cite
|
Sign up to set email alerts
|

Updated Genome Assembly of Bighead Carp (Hypophthalmichthys nobilis) and Its Differences Between Male and Female on Genomic, Transcriptomic, and Methylation Level

Abstract: Cyprinidae is one of the largest family in freshwater fishes, and it is most intensively cultured fish taxon of the world. However, studies about sex determination in this large family is still rear, and one of the reasons is lack of high quality and complete genome. Here, we used nanopore to sequence the genome of a male bighead carp, obtaining contig N50 = 24.25 Mb, which is one of the best assemblies in Cyprinidae. Five males and five females were re-sequenced, and a male-specific region on LG19 was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Heterozygous describes the presence of two different alleles for the same gene, and higher genome heterozygosity leads to a more diverse gene composition and more genes encoding secreted proteins in fungi [ 60 ]. In addition, there are usually differences in the annotated gene numbers between female and male genomes in fishes (e.g., 2.4% for bighead carp [ 18 , 61 ] and 3.5% for O. fasciatus [ 23 ]). Furthermore, the large contig N50 length is conducive to gene annotation, and when contig N50 ranged from 5.2 Mb [ 15 ] to 19.3 Mb [ 58 ], the total genome number of female grass carp can reach 11.3% of the annotated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous describes the presence of two different alleles for the same gene, and higher genome heterozygosity leads to a more diverse gene composition and more genes encoding secreted proteins in fungi [ 60 ]. In addition, there are usually differences in the annotated gene numbers between female and male genomes in fishes (e.g., 2.4% for bighead carp [ 18 , 61 ] and 3.5% for O. fasciatus [ 23 ]). Furthermore, the large contig N50 length is conducive to gene annotation, and when contig N50 ranged from 5.2 Mb [ 15 ] to 19.3 Mb [ 58 ], the total genome number of female grass carp can reach 11.3% of the annotated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Using BUSCO methods to evaluate completeness, we found that the male O. bidens assembled genome contained 97.5% of the complete sequences ( Table S3 ). The high continuity and completeness of the male O. bidens genome will lay a solid foundation for further studies on population genetics, sex-determining mechanisms, sexual dimorphism, growth regulation, and aquaculture breeding [ 61 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high continuity and completeness of the maleO. bidens genome will lay a solid foundation for further studies on population genetics, sex-determining mechanisms, sexual dimorphism, growth regulation, and aquaculture breeding (Fu et al, 2021;Mascali et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some carps, eels and hagfish are well adapted to hypoxia conditions. Even closely related fish species that inhabit the same environment exhibit varied adaption to oxygen concentrations ( Burggren et al, 2019 ; Fu et al, 2021 ; Wang et al, 2022 ). In previous studies, body mass was found to play a role in fish hypoxia tolerance ( Verberk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%